Quantitative PCR technology in chimerism status evaluation after hematopoietic stem cell transplantation - Štingl Janković, Katarina (Array, 2019)
Chimerism status evaluation is one of the most useful methods for the assessment of the hematopoietic stem cell transplantation outcome, since it gives information about engraftment and disease relapse, as well as providing indication for timely interventions such as donor lymphocyte infusions. The aim of this article is to give an overview of the different methods used for chimerism detection, with a especial emphasis on the quantitative PCR (qPCR) based techniques as the newest in line of techniques used for chimerism monitoring. This overview covers a description of the qPCR method as well as a discussion about the advantages this technique offers in comparison to other methods.